The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/md.0000000000009383
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptives caused venous sinus thrombosis complicated with cerebral artery infarction and secondary epileptic seizures

Abstract: Rationale:Venous sinus thrombosis is a special type of cerebrovascular disease. Its incidence is low and its symptoms are lack of specificity. And its early diagnosis and treatment are very difficult.Patient concerns:This paper reported a rare case of a 43-year-old female who presented with cerebral venous thrombosis (CVT) complicated with cerebral artery infarction and secondary epileptic seizures due to oral contraceptives.Diagnoses:The final diagnosis was intracranial venous sinus thrombosis, acute cerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
(15 reference statements)
1
3
1
1
Order By: Relevance
“…Our study indicated that from 82 patients with cerebral venous and sinus thrombosis, 62 patients were female and 30 patients were male. In the proportion of male to female ratio, as we expected the rate of females with CVT was higher, which is compatible with previous studies and it is due to OCP usage and disorders increasing hypercoagulability in women such as antiphospholipid antibody syndrome, 6,[14][15][16] although the rate of CVT in male patients is a little higher than some previous studies. 11,17,18 We found that thromboses in venous and sinuses happen more often in summer or spring than in winter and autumn.…”
Section: Discussionsupporting
confidence: 91%
“…Our study indicated that from 82 patients with cerebral venous and sinus thrombosis, 62 patients were female and 30 patients were male. In the proportion of male to female ratio, as we expected the rate of females with CVT was higher, which is compatible with previous studies and it is due to OCP usage and disorders increasing hypercoagulability in women such as antiphospholipid antibody syndrome, 6,[14][15][16] although the rate of CVT in male patients is a little higher than some previous studies. 11,17,18 We found that thromboses in venous and sinuses happen more often in summer or spring than in winter and autumn.…”
Section: Discussionsupporting
confidence: 91%
“…Oral contraceptives can decrease anticoagulant activity and promote a decrease in tissue plasminogen activator inhibitor and are known to be a risk factor for venous thromboembolism [15]. Although we could not find any inherited or secondary thrombophilia in this case, oral contraceptives might have contributed to formation of embolism.…”
Section: Discussioncontrasting
confidence: 42%
“…Sinus sagittalis thrombosis is a very rare occlusive disease of cerebral sinuses that can be caused by a variety of factors including infections, oral contraceptives, intracranial hypertension, coagulation disorders or neurosurgical operations (Xu et al, 2017; Miao et al, 2018). It has been shown that pretreatment with RNase1 significantly reduced the sinus occlusion rate, comparable to the effect induced by heparin application in rat sinus venous thrombosis models.…”
Section: Exrna In Cns Pathologiesmentioning
confidence: 99%